Appealing Outcomes: A Study for the Overturn Rate of Canada's Appellate Courts - Lubetsky, Michael H.; Krane, Joshua A. (Osgoode Hall Law Journal, 2009)
This commentary discusses the rate at which Canada's appellate courts are overturned by the Supreme Court of Canada. By deconstructing the overturn rate, the authors identify and compare various factors that affect the rate at which appeals are pursued, considered, and allowed. The data reveal that decisions from the British Columbia, Quebec, and Newfoundland & Labrador courts of appeal are overturned more often than those from their counterparts. Conversely, the Ontario and Saskatchewan courts of appeal exhibit overturn rates below the national average. The analysis suggests that the underlying drivers giving rise to the unusually high or low overturn rates, however, differ from province to province, and this provides possible avenues for further investigation.